The effects of transfer on the acquisition of Russian idioms in a first language by students (Eurasian Journal of Philology Science and Education, 2023)
This study looked into the use of first-language knowledge by second-language learners to understand and create idioms in their second language. The author used idioms that were identical, similar, and completely different in both Kazakh and Russian languages in order to determine which were understood and produced most correctly, which caused the most detrimental transfer, what techniques students used to produce unknown idioms, and what the best-known idioms were like.  In addition to determining the meanings of phraseological units, students were able to understand that they are not subject to changes from the order of their place.The subjects of the study were included 80 advanced Russian language learners. The ability to comprehend 15 identical, 15 similar, and 15 different idioms was assessed using a multiple choice test and a definitions test. The tests were administered in two separate groups of 40 participants. Each group underwent a separate statistical analysis because there was interaction between group and idiom type. Identical idioms were found to be the simplest to comprehend and produce. Similar idioms were almost as well understood but displayed interference.Keywords: idioms, transfer, first language, second language, translation.